HUBUNGAN FAKTOR LINGKUNGAN DAN FAKTOR INDIVIDU TERHADAP KELUHAN SICK BUILDING SYNDROME PADA PEGAWAI DI PT PLN (PERSERO) UPP JBB 3 TAHUN 2022 - Erlina Riyantiasis (2023)
Sick Building Syndrome can be related to air contaminants in the room. The results of the preliminary study note that cleaning the air conditioner has not been carried out routinely and periodically, this can cause microorganisms to contaminate the air conditioner and cause disease. The research design used a cross-sectional method. Data was collected through questionnaires and observation. The sample were 41 employees of PT PLN (Persero) UPP JBB 3. The sampling technique uses the total population. This study used univariate and bivariate analysis (Fisher's exact). Bivariate analysis of age (p=1.000), gender (p=0.445), years of service (p=1.000), smoking history (p=1.000), history of allergies (p=0.164), history of COVID-19 (p=0.491), temperature (0.67), humidity (p=1.000), and lighting (p=0.300). The results of the study show that more employees experience SBS. There was no significant relationship between age, gender, years of service, history of smoking, history of allergies, history of COVID-19, temperature, humidity, and lighting with the occurrence of SBS complaints. More employees experience SBS with non-standard room temperature and lighting. It is recommended to always maintain a healthy body condition (exercising and consuming nutritious food) and cleaning the environment (routinely carrying out AC maintenance and servicing with a frequency adjusted to usage).